The Effect of Innovative Behavior and Work Engagement on Performance of Students in Field Work Practice (PKL) at FEBI IAIN Ternate - Zainal Abidin Marasabessy; Hasriyati Fatmona; Hilman Idrus (Lembaga Bale Literasi, 2026)
This study aims to analyze the effect of innovative behavior and work engagement on the individual performance of students from the Faculty of Islamic Economics and Business (FEBI), IAIN Ternate, who participate in Field Work Practice (PKL). This study uses a quantitative approach with a survey method through the distribution of questionnaires to 36 respondents. The data were analyzed using multiple linear regression through SPSS software. The results show that innovative behavior has a positive but not significant effect on performance. In contrast, work engagement has a positive and significant effect on performance. Simultaneously, both variables have a significant effect on performance.